Transcriptional and translational initiation of the glucoamylase and mucin genes in Saccharomyces cerevisiae [microform] - Vivier, Melané Alethea (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD) -- University of Stellenbosch, 1997.